PENGARUH RENUMERASI DAN ETOS KERJA TERHADAP KINERJA PEGAWAI PADA BIRO UMUM SEKRETARIAT UTAMA BADAN PUSAT STATISTIK - Akhmad Junaedi (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
The problem faced by the Central Bureau of Statistics is the remuneration that becomes the dependency of employees and the low work ethic. The problem causes employee performance is not optimal. This research uses quantitative analysis method with simple regression analysis tool, and multiple linear regression. The technique used in this research to obtain data about, is as follows: Interview and Questionnaire / Quesioner. The population of this study is all employees at the Central Bureau of Statistics (BPS), which amounts to 100 people including the Head of Public Bureau. Census sampling technique with sample random sampling and the result of formula used to determine and sampling by Taro Yamane (in Riduwan, 2010: 249). Data analysis using linear regression analysis using SPSS statistical test to see the effect of remuneration and work ethic on Performance of State Civil Apparatus (ASN) at General Bureau of Statistics Center in 2016, with significant 10%.After passing the validity and reliability of the data, obtained the result that states that Remuneration partially affect on employee performance. Similarly, work ethics based on research shows a significant effect on employee performance. Based on the results of the study and research together Remuneration and Working Ethics have a positive and significant impact on Employee Performance on the General Bureau of the Central Bureau of Statistics. Central Bureau of Statistics General Bureau. The regression equation is: Y = 22,917 + 0,123 X1 + 518X2, where every increase of 1 score of variable X1 (remuneration) and X2 (work ethic) will increase employee performance equal to 0,123, and 0,518, assuming other variable is constant,